Forage production with native and hybrid corn (Zea mays). - Elizondo-Salazar, Jorge Alberto (2006)
The experiment was conducted at the Alfredo VolioMata Experiment Station of the University of Costa Rica,located at an altitude of 1542 masl, with an average annualrainfall of 2050 mm. The purpose was to determine totalforage mass of two corn cultivars: hybrid and native,evaluated at the same age and in similar physiological stage.The study determined, in both cultivars, that dry matter yield(kg/ha) reflected an increase when the distance betweenplants was reduced. Cultivar rebounded notably on totalforage mass production. Dry matter yield (kg/ha) was 30%higher in the native that in the hybrid when compared at thesame age. Both cultivars were compared in similarphysiological stage, dry matter yield (kg/ha) was 37% higherin native corn. The height average of the plants was 1,7meters higher in native that in hybrid. No significantdifferences were found for dry and fresh matter on nativecorn at 105 and 133 days of growth.